Análisis multi-resolución y codificación sin pérdida de información en la compresión de señales electrocardiográficas - Ballesteros, Dora M; Gaona, Andrés E (Visión electrónica, 2011)
Many algorithms have been developed in the compression on biomedical signals. One of the most commonly compressed signals correspond to the electrocardiographic signal because is frequently measurement in environment hospitals. In this paper, we present the comparison of two methods based on multi-resolution analysis and lossless encoders, specifically Discrete Wavelet Transform and Huffman-Run length. In the performance of the algorithms, we analyzed two parameters: the compression ratio (CR) and the percentage of roots mean square (PRD). Our algorithms presented a CR of 8:1 to a PRD of 0,5%, which are good results in clinical applications, because the main characteristics in time and frequency are preserved.